Parental Intervention in Educating Basic Knowledge of Sex at Early Childhood - Rahmadhani Fitri; Mega Iswari; Afdal; Mowafg Masuwd (Institut Agama Islam Negeri Madura, 2024)
Sexuality education in early childhood is an important aspect that is often overlooked or considered taboo in many cultures and societies. Proper sex education from an early age is essential to ensure children grow up with a proper understanding of their bodies, interpersonal relationships, and moral values related to sexuality. This study aims to reveal the importance of parents' role in early childhood sexuality education as a foundation in preventing violence and sexual abuse against children. The research method used is a literature study, by identifying, evaluating, and analyzing available information to answer predetermined research questions. The results showed that the family is the first informal educational institution for children, where the role of parents is very central in shaping children's character and behavior, including in terms of sexuality education. Parents are responsible for providing appropriate and relevant information according to the child's developmental stage, as well as instilling strong moral values. However, the main challenge faced by parents is the lack of knowledge and understanding of how to provide proper sex education, as well as the influence of the media that often presents information that is not suitable for children. In conclusion, sex education provided by parents from an early age has an important role in protecting children from the dangers of sexual violence and abuse, so efforts are needed to improve parents' knowledge in this regard.